2016
DOI: 10.1128/aac.03011-15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Kidney Injury among Patients Receiving Concomitant Vancomycin and Piperacillin-Tazobactam: Opportunities for Antimicrobial Stewardship

Abstract: Despite their common use as an empirical combination therapy for the better part of a decade, there has been a recent association between combination therapy with vancomycin and piperacillin-tazobactam and high rates of acute kidney injury (AKI). The reasons for this increased association are unclear, and this analysis was designed to investigate the association. Retrospective cohort and case-control studies were performed. The primary objective was to assess if there is an association between extendedinfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 14 publications
4
58
0
Order By: Relevance
“…To our knowledge, this is the largest study to date to examine the difference in AKI incidence among patients treated with VAN and FEP or PTZ. We found the AKI rate in patients treated with VAN-TZP to be 21.4%, whereas the range of the incidence found in the current literature is 9.5 to 34.8% (8)(9)(10)(11)(12)(13)(14)(15)(16). The AKI incidence in the VAN-FEP group was similar to previous reports of 12.5% (9,10).…”
Section: Discussionsupporting
confidence: 54%
“…To our knowledge, this is the largest study to date to examine the difference in AKI incidence among patients treated with VAN and FEP or PTZ. We found the AKI rate in patients treated with VAN-TZP to be 21.4%, whereas the range of the incidence found in the current literature is 9.5 to 34.8% (8)(9)(10)(11)(12)(13)(14)(15)(16). The AKI incidence in the VAN-FEP group was similar to previous reports of 12.5% (9,10).…”
Section: Discussionsupporting
confidence: 54%
“…The concern for AKI induced with use of TZP and VAN combination therapy raised a new clinical question-does the infusion strategy of TZP affect the incidence of AKI when used concomitantly with VAN? Documented nephrotoxicity rates in patients receiving TZP and vancomycin (VAN) combination therapy are similar, regardless of TZP infusion strategy (8,9). Results of a study including 320 patients performed by Karino and colleagues suggest comparable rates of AKI (32.5% versus 33.1%; P ϭ 1.0) in the prolonged-and intermittent-infusion groups, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
“…McCormick et al completed a retrospective study of 200 patients and did not find a difference in acute kidney injuries (AKIs) between patients receiving intermittent TZP infusions versus those receiving extended infusions (11% versus 9%; P ϭ 0.637) (7). The literature to date suggests similar rates of nephrotoxicity in patients receiving TZP and vancomycin (VAN) combination therapy, regardless of TZP infusion strategy (8,9). No previous studies have reported the impact of prolonged infusions on AKI with ␤-lactams other than TZP.…”
mentioning
confidence: 99%
“…These activate Toll-like 4 receptor, and form inflammatory reaction cascade leading to pathophysiological changes in renal vascular endothelial cells and renal parenchymal cells, and eventually kidney damage [12]. Sepsis patients have changes in their neuroendocrine system such as activation of sympathetic nervous system, release of vasopressin, and activation of renin -angiotensin -aldosterone system.…”
Section: Discussionmentioning
confidence: 99%